The Influence of Taxpayer Awareness and Tax Sanctions on Motor Vehicle Taxpayer Compliance: Employees of Universitas Kristen Indonesia - Ratna Juwita Telaumbanua; Juaniva Sidharta (Jurnal Riset Akuntansi, 2025)
One source of local tax revenue is motor vehicle tax, which according to Article 1 of Law No. 28/2009 is a tax related to transportation affairs and levied by local governments on the ownership or control of motor vehicles. Motor Vehicle Tax (PKB) is one of the sources of tax or levy received by each region. It is given to help the development of the province and improve the welfare of the people.Translated with DeepL.com (free version)The objectives of this study are: 1. Knowing the impact of taxpayer awareness on motor vehicle tax compliance among Employees of Universitas Kristen Indonesia. 2. Analyzing the effect of tax sanctions on motor vehicle taxpayer compliance among employees of the Universitas Kristen Indonesia. This study uses a type of Quantitative research. The location of this research is located in the Campus Environment of the Universitas Kristen Indonesia, Cawang UKI, East Jakarta. This calculation method uses multiple linear regression analysis methods. Data were collected through questionnaires distributed to taxpayers by applying proportionally stratified random sampling techniques. The results showed: 1. The t value of the taxpayer awareness variable (X1) is 2.613> t table 40.159, with the regression coefficient value of the taxpayer awareness variable is 3.354. This means that the higher the awareness of taxpayers owned, the higher the level of taxpayer compliance. 2. The t value of the variable count of the effect of tax sanctions is 2.000> t table 31.577 with the variable regression coefficient value of tax sanctions is 2.637. Where the stricter the tax regulation sanctions imposed, it will increase taxpayer compliance.